Analisis Strategi Pemasaran di UMKM Yahuud Yogurt Kelurahan Sariharjo Kapanewon Ngaglik Kabupaten Sleman - Realita Putri Alfianti; Budiarto Budiarto; Indah Widowati (Agrisociabus, 2022)
The research that was conducted at the Yahuud Yogurt UMKM was aimed at (1) identifying the internal and external factors that became the strengths, weaknesses, opportunities and threats in the Yahuud Yogurt UMKM. (2) To analyze alternative marketing strategies that can be applied to Yahuud Yogurt UMKM. The research method uses a descriptive method with a case study approach. The method of taking respondents used purposive sampling technique and there were 6 selected respondents. Types of data used, primary and secondary data. Data collection methods include observation, interviews, questionnaires, documentation and Forum Group Discussion (FGD). Data analysis techniques used are Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), Internal-External Matrix (IE), and SWOT Matrix and Quantitative Strategic Planning Matrix (QSPM). The results of the study (1) Internal factors, UMKM Yahuud Yogurt has the main strength in the form of a thick yogurt texture, the main weakness is the lack of reliable marketing personnel. External factors are the main opportunities for the development of internet technology, while the main threat is rising prices of raw materials and supporting materials. (2) the priority of marketing strategies that can be applied to Yahuud Yogurt SMEs is a market penetration strategy. Keywords: External Factors, Internal Factor, Marketing Strategi, QSPM, SWOT, Yogurt